2011
DOI: 10.1177/0309364611422269
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic rehabilitation of a patient with partial ear amputation using a self suspension technique

Abstract: Background and Aim: Partial ear amputations are one of the forms of ear loss. A user-friendly design of prosthesis with safe suspension and an aesthetic appearance can be helpful to a patient who has lost part of their ear due to congenital absence or trauma. Prosthetic use has social and psychological effects on the patient and their family. The aim of this paper is to describe a technique of ear prosthesis fabrication with self suspension for these patients. Technique: To provide a snugly fitting prosthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Satisfaction of patients in using prostheses was related to aesthetic nature of the prostheses, color, and fitting of them. 20 The results of this study demonstrated that good fitting and the patient's skin-matched color-fabricated prosthesis provided good satisfaction in using the prosthesis, while according to improvement of suspension in constructed finger prosthesis, the new method of suspension had increased satisfaction rate compared to another prosthesis.…”
Section: Discussionmentioning
confidence: 72%
“…Satisfaction of patients in using prostheses was related to aesthetic nature of the prostheses, color, and fitting of them. 20 The results of this study demonstrated that good fitting and the patient's skin-matched color-fabricated prosthesis provided good satisfaction in using the prosthesis, while according to improvement of suspension in constructed finger prosthesis, the new method of suspension had increased satisfaction rate compared to another prosthesis.…”
Section: Discussionmentioning
confidence: 72%
“…Providing good suspension using an appropriate suspension method is important in aesthetic prostheses. 9 Adhesives and other approaches have historically been used to provide suspension in finger prostheses. 2,6,7 Our study introduced the use of new method of suspension by providing a suction tunnel on the socket of the stump.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In this article, a new method of suspension based on simple application and use of biomedical material was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate suspension method plus a user-friendly design is critical for use of this type of prosthesis. 11,12 In this article, a new method of suspension based on simple application and use of biomedical material was proposed.…”
Section: Discussionmentioning
confidence: 99%